Nilai Tambah pada Ikan Asap Desa Sumber Bakti Kecamatan Darul Makmur Kabupaten Nagan Raya - Rizki, Ari; Athaillah, Teuku (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Sumber Bakti Village, Darul Makmur District, Nagan Raya Regency. With a sub-district area of 1,027.93 km2. One of the businesses that is developing in Sumber Bakti village is the production of processed smoked fish which is carried out by housewives using traditional fish smoking methods. The business that is developing is the one started by Mrs. Sawiyah. This business is engaged in processing fresh fish into smoked fish. With this business, a product with added value is created to generate profits. The aim of this research is to analyze the added value received by business actors. This research uses a research method, namely the hayami method. Has net income for three months worth IDR 4,718,000 from processing smoked fish. The added value obtained from catfish, snakehead and whitefish is IDR 35,644.9,- IDR 27,096.6 and IDR 4,096.6, respectively. The types of smoked fish processed are catfish, snakehead fish and white fish, with added value ratios of 29.70%, 27.09% and 6.82% then at profit levels of around 29.28%, 26.59% and 5, respectively. 16 %. Processing of smoked catfish, snakehead fish with a medium ratio of between 15%-50% to white fish gets a low ratio with a ratio of <15%.